2008
DOI: 10.1002/ange.200801395
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Affinity‐Based Fingerprinting of 14‐3‐3 Isoforms Using a Combinatorial Peptide Microarray

Abstract: Spezifizieren von 14‐3‐3: Ein fragmentbasierter kombinatorischer Peptid‐Mikroarray erzeugt affinitätsbasierte Fingerprints von sieben Säuger‐14‐3‐3‐Isoformen. Motive mit hoher Affinität für die hoch homologen Isoformen wurden identifiziert. Wahrscheinliche 14‐3‐3σ‐spezifische Peptide wurden zudem durch radiometrisches Zwei‐Farben‐Screening identifiziert (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…[7] To our surprise, almost all immobilized compounds, including TCO-OH, showed nearly equal and strong fluorescent-ligand binding towards two non-BET BRDs, namely GCN5L2 and CREBBP, in a concentration-dependent manner (Figure 2 b; see also Figure S7). [14] Herein, we showed that this process can be used to discriminate between BET bromodomains (e.g., BRD2-4, BRDT) and other BRDs (e.g., PCAF, TAF1L, WDR9). In the meantime, we carried out concentration-dependent microarray K d determination against all 12 BRDs (Figure 2 c and Figure S6), and the results were further extrapolated to obtain the corresponding app K d (app K d = apparent K d ; Figure 2 d).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…[7] To our surprise, almost all immobilized compounds, including TCO-OH, showed nearly equal and strong fluorescent-ligand binding towards two non-BET BRDs, namely GCN5L2 and CREBBP, in a concentration-dependent manner (Figure 2 b; see also Figure S7). [14] Herein, we showed that this process can be used to discriminate between BET bromodomains (e.g., BRD2-4, BRDT) and other BRDs (e.g., PCAF, TAF1L, WDR9). In the meantime, we carried out concentration-dependent microarray K d determination against all 12 BRDs (Figure 2 c and Figure S6), and the results were further extrapolated to obtain the corresponding app K d (app K d = apparent K d ; Figure 2 d).…”
mentioning
confidence: 93%
“…[12] This is critical for the study of moderate or weak PPIs, such as those between BRDs and their ligands, for example, between acetylated peptides and benzodiazepines. Our previously developed strategy of using the biotin-avidin interaction for compound immobilization met some of these requirements, [11,14] but failed to provide sufficiently intense signals for fluorescence detection (not shown), which is likely due to low compound loading of the surface. Our previously developed strategy of using the biotin-avidin interaction for compound immobilization met some of these requirements, [11,14] but failed to provide sufficiently intense signals for fluorescence detection (not shown), which is likely due to low compound loading of the surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, proteases have high requirements for displaying bioactivity, and they are detected not only by their bindings activities but rather by their enzymatic activities 36. This paves the road to use linker of PEG as a linker to achieve better accessibility of the immobilized biomolecules 11, 20, 23, 25, 26, 37…”
Section: Introductionmentioning
confidence: 99%
“…Based on the amino acid sequence, RFRpSYPP, that has previously been shown as optimal for 14-3-3 binding, a library of small-molecule/peptide hybrids was synthesised in which either 50 diverse amines were coupled to the N-terminal peptide sequence (RFRpS) or 243 diverse acid building blocks were coupled to the C-terminal peptide sequence (pSYPP). [8] The resulting 293 single hybrids were spotted onto a glass slide, and the binding of fluorescently labelled GST-14-3-3 (isoform sigma) was measured. Five compounds showed robust 14-3-3 binding.…”
mentioning
confidence: 99%